Islamic securities market-economic growth nexus: evidence from Indonesia - Abduh, Muhamad (2012)
The purpose of this study is to evaluate the dynamic effects of Islamic securities markets development on economic growth, particularly in Indonesia. The model estimation used to uncover the relationship is autoregressive distributed lag (ARDL). This study uses quarterly time series data [2000:Q1-2011:Q4] for the variable of Jakarta Islamic Index to represent Islamic securities and real GDP. The result shows that the relationship is following supply-leading view, which means that there is evidence of long run influence of Islamic securities markets development towards Indonesia economic growth but not vice versa. Hence, developing Islamic financial markets can be one way to boost the economy in Indonesia.